2012
DOI: 10.1007/s13311-012-0107-z
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Manipulation of Cell Death and Neuroplasticity Pathways in Traumatic Brain Injury

Abstract: Traumatic brain injury (TBI) initiates a complex cascade of secondary neurodegenerative mechanisms contributing to cell dysfunction and necrotic and apoptotic cell death. The injured brain responds by activating endogenous reparative processes to counter the neurodegeneration or remodel the brain to enhance functional recovery. A vast array of genetically altered mice provide a unique opportunity to target single genes or proteins to better understand their role in cell death and endogenous repair after TBI. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 122 publications
0
21
0
Order By: Relevance
“…Since activitydependent regulation of gene expression is critical for inhibitory network remodeling through life experiences [29,30], it is possible that beneficial effects of an enriched environment might be related to its ability to enhance neuronal viability or possibly by providing sufficient compensatory inhibition to the overexcited hippocampal circuitry. Finally, our results revealed that there was no colocalization of caspase-3 and PV interneurons, suggesting that caspase-independent pathways may be involved in mediation of the decreased PV expression induced by sevoflurane [35]. Also, there was no colocalization of BrdU and PV interneuron, indicating the abnormalities of PV interneurons were not due to the effect of sevoflurane on the proliferating cells.…”
Section: Discussionmentioning
confidence: 58%
“…Since activitydependent regulation of gene expression is critical for inhibitory network remodeling through life experiences [29,30], it is possible that beneficial effects of an enriched environment might be related to its ability to enhance neuronal viability or possibly by providing sufficient compensatory inhibition to the overexcited hippocampal circuitry. Finally, our results revealed that there was no colocalization of caspase-3 and PV interneurons, suggesting that caspase-independent pathways may be involved in mediation of the decreased PV expression induced by sevoflurane [35]. Also, there was no colocalization of BrdU and PV interneuron, indicating the abnormalities of PV interneurons were not due to the effect of sevoflurane on the proliferating cells.…”
Section: Discussionmentioning
confidence: 58%
“…Recent studies also demonstrate a potential second peak of inflammation till 2 months after injury as well as chronic neuroinflammatory changes ( 6 , 71 ). Additional damage can occur at a distance over days and months after injury via Wallerian degeneration and/or demyelination, reflecting CNS connectivity ( 54 , 65 ).…”
Section: Mechanisms Of Traumatic Injury To the Cnsmentioning
confidence: 99%
“…Given this delayed onset, it is possible that secondary injuries may be prevented and are considered to be potential pharmaceutical targets to improve TBI outcomes [24]. These secondary mechanisms represent complex, parallel, interacting and interdependent injury processes that remain poorly understood, with no pharmacological treatment known to effectively limit their progression and improve TBI patient outcome.…”
Section: Basic Pathophysiology Of Tbimentioning
confidence: 99%